Compression-tolerant supercapacitor based on NiCo2O4/Ti3C2Tx MXene/reduced graphene oxide composite aerogel with insights from density functional theory simulations - Zhang, Maozhuang; Jiang, Degang; Jin, Fuhao; Sun, Yuesheng; Wang, Jianhua; Jiang, Mingyuan; Cao, Jiangyong; Zhang, Bo; Liu, Jingquan (Journal of colloid and interface science, 2023)
[Display omitted] •The NCO/MGA-300 has excellent elastic properties and compressive durability.•DFT calculations prove that NCO/MGA-300 has better electrochemical performance.•The NCO/MGA-300 has superb specific capacitance, rate performance and stability.•The aNCMSC shows stable electrical properties after 100 compression-release cycles. Compression-tolerant electrodes are critical for developing next-generation wearable energy storage devices. However, most of previous studies on compressible electrodes focus on carbon-based materials, whereas metal-based materials such as spinel metal oxide with faradaic nature have been rarely studied due to their lack of compressibility. Herein, NiCo2O4 (NCO) microtubes assembled by ultrathin and mesoporous nanosheets, are deposited on/into Ti3C2Tx MXene/reduced graphene oxide aerogel (MGA), an intrinsically compressible host template with high conductivity and specific surface areas. The optimized NCO/MGA-300 sample shows a reversible compressive strain of 60% and a superior durability. Density functional theory (DFT) calculations reveal that the NCO/MGA-300 heterojunction has high electronic conductivity, fast electron transfer ability, and low adsorption energy for OH– ions. As a result, the NCO/MGA-300 electrode exhibits superb electrochemical performance in terms of its high gravimetric capacitance (1633F g−1 at 1 A g−1), rate performance (1492F g−1 at 10 A g−1), and remarkable cycling stability of 86.6% after 10,000 charge-discharging cycles. Moreover, an assembled asymmetric supercapacitor based on compressible NCO/MGA-300 shows stable electrochemical performances under different compressive strains (20%. 40% and 60%), or after 100 compression-release cycles. This research finding demonstrates the possibility of metal-based electrode for wearable devices with high energy storage capability and good compressibility.